Common Training Practices and Preferred Personality Traits of Intramural Sports Officials. Issue 1 (April 2018) - Walker, Joseph; Walker, Laura; Dietrich, Joshua; Dotterweich, Andrew; Davis, Jason; Collins, John
This research study examined campus recreation intramural training techniques used to prepare sports officials. The top 10 techniques reported by the sample (n = 52) are presented. Use of National Intramural-Recreational Sports Association (NIRSA) training materials was found to have a significant positive relationship with overall official training program satisfaction. Intramural coordinators who self-rated as unsatisfied with training program also rated their program significantly less effective when compared to intramural coordinators who indicated satisfaction with their training program. Further inquiry determined that the responding professionals ranked officials' traits and abilities similar in importance, with confidence, knowledge, and decision making as most important. There were no differences in the preferred officials' trait ratings when compared to overall program satisfaction.